2012
DOI: 10.4049/jimmunol.1103293
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Leukocyte Proteinase Inhibitor-Competent DNA Deposits Are Potent Stimulators of Plasmacytoid Dendritic Cells: Implication for Psoriasis

Abstract: Secretory leukocyte proteinase inhibitor (SLPI) is a well-established inhibitor of serine proteases such as human neutrophil elastase (HNE) and a NF-κB regulatory agent in immune cells. In this paper, we report that SLPI plays a previously uncharacterized role in regulating activation of plasmacytoid dendritic cells (pDCs). As the main source of IFN type I (IFNI), pDCs are crucial contributors to inflammatory and likely wound-healing responses associated with psoriasis. The mechanisms responsible for activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 39 publications
(54 reference statements)
1
61
0
1
Order By: Relevance
“…Under certain conditions, moreover, neutrophils express MHC class II molecules such as HLA-DR, which may allow neutrophils to interact directly with T-cells and participate in antigen presentation and T-cell activation [24,57-59]. Post-apoptotic neutrophils within the epidermis may also provide a source of autoantigens by the formation of neutrophil extracellular traps (NETs) consisting of a web-like chromatin structure, human neutrophil elastase (HNE), cathelicidin (LL37), and secretory leukocyte proteinase inhibitor (SLPI) [60-62]. These NET components provide DNA complexes that can enhance pDC activation and production of cytokines such as IFN-α [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under certain conditions, moreover, neutrophils express MHC class II molecules such as HLA-DR, which may allow neutrophils to interact directly with T-cells and participate in antigen presentation and T-cell activation [24,57-59]. Post-apoptotic neutrophils within the epidermis may also provide a source of autoantigens by the formation of neutrophil extracellular traps (NETs) consisting of a web-like chromatin structure, human neutrophil elastase (HNE), cathelicidin (LL37), and secretory leukocyte proteinase inhibitor (SLPI) [60-62]. These NET components provide DNA complexes that can enhance pDC activation and production of cytokines such as IFN-α [60].…”
Section: Discussionmentioning
confidence: 99%
“…Post-apoptotic neutrophils within the epidermis may also provide a source of autoantigens by the formation of neutrophil extracellular traps (NETs) consisting of a web-like chromatin structure, human neutrophil elastase (HNE), cathelicidin (LL37), and secretory leukocyte proteinase inhibitor (SLPI) [60-62]. These NET components provide DNA complexes that can enhance pDC activation and production of cytokines such as IFN-α [60]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, a role for NETs in early innate immunity is strongly supported. However, NET formation may also play a role in adaptive immune responses, as it was demonstrated that NETs stimulate plasmacytoid dendritic cells (36). Additionally, NETs were shown to prime T cells by reducing their threshold for activation (37).…”
Section: Discussionmentioning
confidence: 99%
“…3 EVs are cell-derived membrane vesicles of heterogeneous size, containing hundreds of distinct proteins, lipids, and microRNAs, 41 that have been shown to mainly down-modulate the inflammatory responses in activated DCs (Table 1). In this context, recent publications have reported that NETs can also mediate cross-talk between neutrophils and several DC subsets and suggested that they represent a novel mechanism involved in the pathogenesis of SLE 42,43 and psoriasis in humans, 44,45 or type 1 diabetes (T1D) 46 and autoimmune vasculitis 47 in mice. Interestingly, inhibitory effects of NETs on lipopolysaccharide (LPS)-induced DC maturation and cytokine production have also been observed, given that NET-treated DCs inhibit T-lymphocyte proliferation and skew T-cell differentiation toward a T-helper type 2 (Th2) phenotype (L. S. Barrientos, V. Marin-Esteban, and S. Chollet-Martin, unpublished data, 2014).…”
Section: Cross-talk Between Neutrophils and Innate Immune Cellsmentioning
confidence: 99%